Genomic Insights Into the Interspecific Diversity and Evolution of Mobiluncus, a Pathogen Associated With Bacterial Vaginosis - Li, Yisong; Wang, Ying; Liu, Jie (Frontiers in Microbiology, 2022)
Bacterial vaginosis (BV) is a common vaginal infection and has been associated with increased risk for a wide array of health issues. BV is linked with a variety of heterogeneous pathogenic anaerobic bacteria, among which Mobiluncus is strongly associated with BV diagnosis. However, their genetic features, pathogenicity, interspecific diversity, and evolutionary characters have not been illustrated at genomic level. The current study performed phylogenomic and comparative genomic analyses of Mobiluncus. Phylogenomic analyses revealed remarkable phylogenetic distinctions among different species. Compared with M. curtisii, M. mulieris had a larger genome and pangenome size with more insertion sequences but less CRISPR-Cas systems. In addition, these two species were diverse in profile of virulence factors, but harbored similar antibiotic resistance genes. Statistically different functional genome profiles between strains from the two species were determined, as well as correlations of some functional genes/pathways with putative pathogenicity. We also showed that high levels of horizontal gene transfer might be an important strategy for species diversification and pathogenicity. Collectively, this study provides the first genome sequence level description of Mobiluncus, and may shed light on its virulence/pathogenicity, functional diversification, and evolutionary dynamics. Our study could facilitate the further investigations of this important pathogen, and might improve the future treatment of BV.